Optimization of Safe Work Implementation through Improving Work Discipline and Compliance Personal Protective Equipment Use among Oil Palm Plantation Workers - Fakhrurradhi Luthfi; Safrizal Safrizal; Muhammad Iqbal Fahlevi; Ihsan Murdani; Fadhil Ilhamsyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Oil palm plantations represent an occupational sector with a high risk of workplace accidents due to exposure to various hazards, including injuries from work equipment, chemical exposure, impacts from falling fresh fruit bunches, slips and falls, musculoskeletal disorders, and low compliance with the use of personal protective equipment (PPE). These conditions contribute to a high incidence of occupational accidents and reduced worker productivity. This community service program aimed to improve workers' knowledge, work discipline, and compliance with PPE use among oil palm plantation workers. A participatory approach was employed through educational sessions, demonstrations of proper PPE use, interactive discussions, and evaluation using pretest and posttest assessments. The program was conducted on June 5, 2026, at the UD Tamita Warehouse, Kuala Tuha Lamie Road, Kuala Trang Village, involving 30 oil palm plantation workers. The evaluation results demonstrated significant improvements in workers' knowledge and understanding of occupational safety and health (OSH), the importance of PPE, and adherence to safe work procedures. PPE compliance increased from 23.33% before the intervention to 83.33% after the educational and demonstration sessions. These findings indicate that participatory education combined with hands-on practice is effective in promoting safe work behaviors among oil palm plantation workers. Therefore, continuous OSH education and training programs should be implemented to strengthen the workplace safety culture, improve PPE compliance, and reduce the risk of occupational accidents in oil palm plantation settings.